2010
DOI: 10.1021/ef9010934
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Preparation of Emulsions Derived from Aqueous Bio-oil Fraction and 0# Diesel and Combustion Characteristics in Diesel Generator

Abstract: Preparation of emulsions from aqueous fractions of biomass pyrolysis liquid (bio-oil) and 0# diesel was studied under ultrasonic power. The thermogravimetric analysis and combustion characteristics of the optimized emulsions in a particular diesel generator were also investigated. The results show that the mass ratio of aqueous bio-oil fraction to 0# diesel affected the emulsion stability greatly, by factor analysis method, and the optimized emulsion was not stratified for 30 days when the ratio was 1:9 under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This may be attributed to the fact that the ultrasonic-assisted extraction with water can more effectively extract oxygenated compounds (e.g., phenolic compounds) from algal biocrude oil. 31,47 The effect of the mixing ratio of the toluene-soluble fraction (liquid phase) and water during the ultrasonic-assisted extraction was also investigated. An ultrasonication time of 15 min was selected because the nitrogen content of algal biocrude oil can be effectively reduced under this condition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributed to the fact that the ultrasonic-assisted extraction with water can more effectively extract oxygenated compounds (e.g., phenolic compounds) from algal biocrude oil. 31,47 The effect of the mixing ratio of the toluene-soluble fraction (liquid phase) and water during the ultrasonic-assisted extraction was also investigated. An ultrasonication time of 15 min was selected because the nitrogen content of algal biocrude oil can be effectively reduced under this condition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To conduct an efficient emulsification, certain amounts of water and the toluenesoluble phase would be needed to create a stable micelle and reach the critical micelle concentration. 31,44,47,48…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is supposed that the solid phase may play a role in promoting evaporation such as boiling stone. Therefore, the water phase in the emulsion may explosively evaporate and cause secondary atomization both the emulsion and the water phase [21,22] with increase in the concentration. As a result, the higher the concentration of the solution was, the smaller both primary and agglomerated particle would become.…”
Section: Production Of Nickel Oxide Particle By W/o Emulsion Combustionmentioning
confidence: 99%
“…Yuping Li [17] has studied the emulsification of the aqueous fractions of bio-oil (ABF) and 0# diesel under ultrasonic power. It reported that the mass ratio of ABF to 0# diesel affected the emulsion stability greatly, by factor analysis method, and the optimized emulsion was not stratified for 30 days when the ratio was 1:9 under the following conditions: water: bio-oil mass ratio, 2:1; ultrasonic time, 120 min; formula emulsifier addition (Span-80:Tween-80:Tween-20:n-octanol ratio= 72:9:9:10, wt%), 3wt%.…”
Section: A Introductionmentioning
confidence: 99%